Implementasi Merdeka Belajar melalui Pelatihan Modul Ajar Berdiferensiasi bagi Guru SMPK Materdai Probolinggo - Darwin Djeni; Eko Waluyo (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
This Community Service Activity aims to improve the competence of SMP K Materdai teachers in designing and compiling teaching modules that apply the principles of differentiated learning in accordance with the direction of the Merdeka Belajar policy. Differentiated learning is an approach that adjusts the process, content, and learning products based on the needs, interests, and learning profiles of students. Through this training, teachers are given a conceptual understanding and practical skills in developing adaptive and contextual teaching modules. The activity methods used include socialization, interactive discussions, module preparation practices, and formative feedback. The results of the activity show an increase in teachers' understanding and ability in compiling applicable differentiated teaching modules. This training is a concrete step in supporting the implementation of the Merdeka Curriculum and improving the quality of the learning process in schools. The sustainability of the activity is planned through continued mentoring and collaboration in developing teacher learning communities.